P16 and P53 Expression in Esophageal Squamous Cell Carcinoma: A Brief Report From The Experience of South of Iran, and Review of the Literature - Bita Geramizadeh; Alireza Mohammadian; Alireza Shojazadeh; Sahand Mohammadzadeh (SAGE Publishing, 2021)
Background: Iran is one of the high-risk countries for esophageal squamous cell carcinoma (ESCC). Human papillomavirus (HPV) has been reported as one of the etiologic, pathogenetic, and prognostic factors in this tumor, especially in high-risk geographic areas. Previous reports from our geographic area, that is, the South of Iran failed to show any evidence of HPV in the cases of ESCC by molecular methods. Objectives: In this study, we evaluated P16 and P53 immunohistochemistry (IHC) expression in the cases of esophageal ESCC from Fars province in the South of Iran to find the presence of any correlation between clinicopathologic findings with P16 and P53 expression by IHC as etiologic and prognostic biomarkers. We also tried to compare the results from other geographic areas of Iran and the world. Results: P16 and P53 expression were found in 42.9% and 66.12% of ESCCs, respectively. No statistically significant correlation was found between clinicopathologic findings and P16 pr P53 expression. Conclusion: Although P16 and P53 expression in ESCC in the South of Iran is significant, there is no statistically significant correlation between clinicopathologic findings and outcome in ESCC and expression of these 2 proteins to be considered as biomarkers. Results from other geographic areas of Iran and the world are also very controversial and inconsistent.